MANAGEMENT OF METAL SCRAP AND METAL WASTE FOR THE TRANSITION TO CIRCULAR ECONOMY AND THE RECOVERY OF UKRAINE - Скуйбіда, О.Л.; Гаркуша, М. (Управління змінами та інновації, 2023)
In the modern world, the production of metal products requires significant energy and raw materials, which leads to serious economic losses and environmental damage. The article considers the problem of recycling in the metallurgical industry to reduce the negative impact on the environment and improve economic indicators. Nowadays the problem of scrap metal disposal is an urgent issue for Ukraine especially due to the military actions on its territory. This is an additional challenge for the domestic economy, which is prompting a shift from a linear economic structure to a circular one. The European countries are already actively moving towards the 10R principles for the circular “green” economy by introducing up-to-date legislation and implementing proper organizational, scientific and technological measures. Ukraine has already adopted some documents regarding sustainable development and circular economy such as the National Waste Management Strategy, the Strategy of the State Environmental Policy of Ukraine, the Concept for the Implementation of the State Policy in the Field of Climate Change, the Strategy for Low-Carbon Development of Ukraine, etc. Nevertheless there is no proper legislative framework for specific circular economy measures and recycling of metal scrap and waste in our country.